Pengaruh Gaya Kepemimpinan dan Budaya Organisasi terhadap Kinerja Karyawan (Studi pada PO Dedy Jaya Brebes Tahun 2016–2018) - Tahta Alfina; Azizah Indriyani; Ari Kristiana; Indah Dewi Mulyani; Khalid Iskandar (Program Studi Manajemen Universitas Muhadi Setiabudi, 2019)
The abstracts of human resources have a very important position in running the wheels of the organization’s life, the success of an organization will not be separated from how competent human resources they have. Efforts to improve several factors namely leadearship style, and organizatonal bidya on employee performance. In this study, researchers had the opportunity to carry out research on PO Dedy Jaya Brebes.The purpose of this study is to explain or explain the final project with the title influence of leadership style and organizational culture on employee performance on the PO Dedy Jaya Brebes, This type of research is quantitative. The population and sample in this study were 50 employees of PO Dedy Jaya Brebes. The determination of the sampel in this study was using the simple random simple random sampling method. Data collection tools in this study are primary data, secondary data, questionnaires, and interviews. The analytical method used is quantitative data analysis, descriptive analysis, of linear regression analysis, correlation analysis and partial correlation analysis, with the help of SPSS.